2016
DOI: 10.1111/poms.12552
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous Submission Behavior and its Implications for Success in Innovation Contests with Public Submissions

Abstract: I nnovation contests are increasingly adopting a format where submissions are viewable by all contestants and the information structure changes during the contest. In such an "unblind" format, contestants must weigh the costs of revealing their submissions against the benefits of improving their submissions through emerging information. We take a closer look at how contestants solve problems in innovation contests with public submission of solutions-that is, unblind contests, by examining the implications of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
82
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(89 citation statements)
references
References 50 publications
(97 reference statements)
5
82
0
Order By: Relevance
“…Our results support previous studies, where the importance of managers in innovation communities has been identified as crucial in ensuring a constructive process that produces the desired outcomes for managers, thereby enabling them to engage in quick interventions and track progress (Dahl et al, 2011). Second, our study also supported the claims that feedback provided by platform moderators shortly after an idea submission is positively associated with active participation and that longer active participation in platform interactions positively benefits the participants (Bockstedt, Druehl, & Mishra, 2016;Wooten & Ulrich, 2017).…”
Section: Linking Sna and Content Analysissupporting
confidence: 89%
“…Our results support previous studies, where the importance of managers in innovation communities has been identified as crucial in ensuring a constructive process that produces the desired outcomes for managers, thereby enabling them to engage in quick interventions and track progress (Dahl et al, 2011). Second, our study also supported the claims that feedback provided by platform moderators shortly after an idea submission is positively associated with active participation and that longer active participation in platform interactions positively benefits the participants (Bockstedt, Druehl, & Mishra, 2016;Wooten & Ulrich, 2017).…”
Section: Linking Sna and Content Analysissupporting
confidence: 89%
“…The growing body of research on crowdsourcing contests has studied contestant behaviors, including entry (Araujo 2013), effort (Huang et al 2012), and submission timing (Bockstedt et al 2016;Yang et al 2010). From a contest host's perspective, predictors of contest outcomes can be either static or time varying throughout the contest.…”
Section: Literature Reviewmentioning
confidence: 99%
“…), transparency level of the identity of participants and submissions (Bockstedt et al. ), feedback mechanism (Mihm and Schlapp , Wooten and Ulrich ), and incentive and award structure (Ales et al. , , Erat and Krishnan , Körpeoğlu and Cho ); see Ales et al.…”
Section: Inclusive Innovation: An Operations Lensmentioning
confidence: 99%